EFEKTIVITAS PEMBELAJARAN AL-QUR'AN HADITS KELAS VIII DI MTs AL FALAH PESISIR TENGAH KABUPATEN PESISIR BARAT - Mutiara Citra; Asri Sanjaya; Andi Sugiartu (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2023)
This research is motivated by the lack of students' attention to the importance of reading the Qur'an, so that its effectiveness has not been well understood. This type of research is descriptive qualitative where there is a relationship between one variable, namely in this study there is an influence on the effectiveness of the habituation of learning Al-Qur'an Hadith at MTs Al-Falah Krui. The purpose of this study was to determine the effect of the effectiveness of learning the Qur'an Hadith in class VIII students of MTs Al-Falah Krui in 2022. The data collection method in this study used a questionnaire. The population in this study were all students of class VIII MTs Al-Falah Krui with a total of 64 students, then samples were taken using Cluster Random Sampling so that a sample of 24 students was obtained. The results of research on the effectiveness of learning the Al-Qur'an Hadith in class VIII students of MTs Al-Falah Krui, the following conclusions can be drawn: achievement of curriculum targets, student absorption, teacher presence, student presence, and student achievement in Al- Qur'an Hadith class VIII MTs Al Falah Krui is above 75%, so that the overall target achievement in the subject of Al-Qur'an Hadith MTs Al Falah Krui is efficient.